2005
DOI: 10.1103/physrevb.72.233104
|View full text |Cite
|
Sign up to set email alerts
|

Orbital ordering inLa0.5Sr1.5MnO4studied by model Hartree-Fock calculation

Abstract: We have investigated orbital ordering in the half-doped manganite La0.5Sr1.5MnO4, which displays spin, charge and orbital ordering, by means of unrestricted Hartree-Fock calculations on the multiband p-d model. From recent experiment, it has become clear that La0.5Sr1.5MnO4 exhibits a crosstype (z 2 − x 2 /y 2 − z 2 ) orbital ordering rather than the widely believed rod-type (3x 2 − r 2 /3y 2 − r 2 ) orbital ordering. The calculation reveals that cross-type (z 2 − x 2 /y 2 − z 2 ) orbital ordering results from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…the electron density at bridge sites increases) without greatly affecting the type of the OO (not shown). Here we would like to emphasize that our findings concerning the nature of spin and OO, as well as rather weak charge order, agree with the recent Hartree-Fock calculations on the multiband d-p model, 58 indicating that the local Coulomb interactions and superexchange suffice already to stabilize the CE phase. There is no doubt, however, that the oxygens distortions also contribute to the stability of this phase, 46,58 and would expand the regions of the CE phase in the phase diagrams shown in the next Section.…”
Section: Orbital and Charge Order At Half Dopingsupporting
confidence: 90%
See 2 more Smart Citations
“…the electron density at bridge sites increases) without greatly affecting the type of the OO (not shown). Here we would like to emphasize that our findings concerning the nature of spin and OO, as well as rather weak charge order, agree with the recent Hartree-Fock calculations on the multiband d-p model, 58 indicating that the local Coulomb interactions and superexchange suffice already to stabilize the CE phase. There is no doubt, however, that the oxygens distortions also contribute to the stability of this phase, 46,58 and would expand the regions of the CE phase in the phase diagrams shown in the next Section.…”
Section: Orbital and Charge Order At Half Dopingsupporting
confidence: 90%
“…Here we would like to emphasize that our findings concerning the nature of spin and OO, as well as rather weak charge order, agree with the recent Hartree-Fock calculations on the multiband d-p model, 58 indicating that the local Coulomb interactions and superexchange suffice already to stabilize the CE phase. There is no doubt, however, that the oxygens distortions also contribute to the stability of this phase, 46,58 and would expand the regions of the CE phase in the phase diagrams shown in the next Section. At the same time realistic oxygens distortions would also modify somewhat the type of occupied orbitals, but the essential features of the orbital order in the CE phase, see Fig.…”
Section: Orbital and Charge Order At Half Dopingsupporting
confidence: 90%
See 1 more Smart Citation
“…A model calculation for a ground state shows a 0.3% increase in the ratio of d 3z 2 −r 2 /(d 3x 2 −r 2 or d 3y 2 −r 2 ) under 0.8 mJ/cm 2 excitation based on the observed structural changes [18,19]. Combining all the observations, Fig.…”
Section: X-ray Identification Of Thermally Inaccessible "Photo-inducementioning
confidence: 56%
“…4,5 The rod-type orbital order is in agreement with the x-ray scattering measurements as well as an earlier theoretical study, but is different from the cross-type order suggested in Refs. 8,9. Exact diagonalization and tight-binding model studies allowed us to examine the interplay between the various energy terms and revealed the reason for the particular orbital order.…”
Section: Discussionmentioning
confidence: 99%